Can MR enterography screen for perianal disease in pediatric inflammatory bowel disease?. Issue 6 (14th November 2017) - AlSabban, Zehour; Carman, Nicholas; Moineddin, Rahim; Lo, Ryan T.; King, Sebastian K.; Langer, Jacob C.; Walters, Thomas D.; Griffiths, Anne M.; Church, Peter C.; Greer, Mary‐Louise C.
Abstract : Background: Pediatric Crohn's disease is associated with perianal disease (PAD). Magnetic resonance enterography (MRE) assesses small bowel involvement in pediatric inflammatory bowel disease (PIBD). Pelvic MRI (P‐MRI) is the gold standard for assessing PAD. Purpose: To determine if MRE can accurately detect PAD in PIBD, distinguishing perianal fistulae (PAF) from perianal abscesses (PAA), referenced against P‐MRI. Study Type: Retrospective. Population: Seventy‐seven PIBD patients, 27 females (mean age 14.1 years), with P‐MRI and MRE within 6 months. Field Strength/Sequence: 1.5T and 3T; P‐MRI: sagittal fat suppressed (FS) T2 fast spin‐echo (FSE), coronal short tau inversion recovery, axial T1 FSE, coronal and axial postcontrast FS T1 FSE; MRE: coronal balanced steady‐state free‐precession (SSFP), coronal cine SSFP, coronal and axial single‐shot T2 FS, axial SSFP, coronal ultrafast 3D T1 ‐weighted gradient echo FS (3D T1 GE), axial diffusion‐weighted imaging, coronal and axial postcontrast 3D T1 GE FS. Assessment: Two radiologists independently, then by consensus, assessed randomized MRI exams, recording PAF number, location, and length; and PAA number, location, length, and volume. Sensitivity analysis used clinical disease as the gold standard, calculated separately for P‐MRI and MRE. Statistical Tests: Comparing MRE and P‐MRI consensus data, sensitivity, specificity, positive, and negative predictive values (P/NPV) were calculated. Inter‐ and intrareader reliability were assessed using kappa statistics. Results: P‐MRI and MRE were paired, detecting PAD in 73 patients, PAF in 63, and PAA in 31 P‐MRI. MRE sensitivities, specificities, PPV, and NPV were: PAD 82%, 100%, 100%, 23%; PAF 74%, 71%, 92%, 38%; PAA 51%, 85%, 69%, 72%; clinical 82%, 22%, 37%, 69%; clinical P‐MRI 96%, 8%, 37%, 80%. MRE interreader agreement for PAD was moderate (kappa = 0.51 [0.29–0.73]), fair for PAF and PAA. Data Conclusion: Using a standard technique, MRE can detect PAD with high specificity and moderate sensitivity in PIBD, missing some PAF and small PAA. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1638–1645.